2012
DOI: 10.1155/2012/527673
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Physiological Responses ofPhaseolusSpecies to Salinity Stress

Abstract: This paper reports the changes on growth, photosynthesis, water relations, soluble carbohydrate, and ion accumulation, for two salt-tolerant and two salt-sensitive Phaseolus species grown under increasing salinity (0, 60 and 90 mM NaCl). After 20 days exposure to salt, biomass was reduced in all species to a similar extent (about 56%), with the effect of salinity on relative growth rate (RGR) confined largely to the first week. RGR of salt-tolerant species was reduced by salinity due to leaf area ratio (LAR) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
27
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 41 publications
6
27
2
Order By: Relevance
“…Growing evidences indicate that abnormal accumulation of Na + and/or K + deficiency severely disrupts photosynthetic capability and impeded translocation of photosynthates from leaves into sink organs [36,57,63], and might be one of the prime reasons for reduction in photosynthetic capacity during salt-sensitivity of the present genotypes. In salt-sensitive Phaseolus species, K + deficiency combined with salt stress induced a reduction in CO 2 photo assimilation and stomata closure [62]. Similar situation was encountered in salt-sensitive genotypes and mutant lines of grass pea experiencing different NaCl-treatment regimes [39,41,55].…”
Section: ] and Phaseolus Aureusmentioning
confidence: 62%
See 2 more Smart Citations
“…Growing evidences indicate that abnormal accumulation of Na + and/or K + deficiency severely disrupts photosynthetic capability and impeded translocation of photosynthates from leaves into sink organs [36,57,63], and might be one of the prime reasons for reduction in photosynthetic capacity during salt-sensitivity of the present genotypes. In salt-sensitive Phaseolus species, K + deficiency combined with salt stress induced a reduction in CO 2 photo assimilation and stomata closure [62]. Similar situation was encountered in salt-sensitive genotypes and mutant lines of grass pea experiencing different NaCl-treatment regimes [39,41,55].…”
Section: ] and Phaseolus Aureusmentioning
confidence: 62%
“…Excessive accumulation of Na + in leaves has been considered highly harmful for normal metabolism of plant, and tolerant genotype has the capacity of successful salt exclusion [13,36]. Salt stress also impairs K + uptake of plants, and it has been suggested that K + deficiency might be a contributing factor to salt-induced growth inhibition through induction of oxidative stress and related cell damage [57,61,62]. The K + : Na + ratio has been used as a discriminating factor between tolerant and sensitive genotypes with greater capacity of former to block or reduce the uptake or exclude the excess amount of Na + and associated increase in K + content [36].…”
Section: ] and Phaseolus Aureusmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduction in crop production observed in various plant species exposed to salt stress is linked to the decline in photosynthesis (Long & Baker, 1986;Chaves et al, 2009). Reduction in the photosynthetic capability of various plant species by salt stress has been documented in a number of reports (Dubey, 1997;Jamil et al, 2007a;Bayuelo-Jimenez et al, 2012). The inhibition in photosynthesis under saline condition can also be explained by the decline in chlorophyll content (Delfine et al, 1999;Jamil et al, 2007).…”
Section: Introductionmentioning
confidence: 98%
“…The decrease in crop performance detected in various plant groups exposed to salinity is linked to the decline in photosynthesis. Reduction in the photosynthetic capability of various plant species by salt stress has been documented in a number of reports [21,22,23]. Foliar supply of manganese (Mn) in suitable quantity may result an increase in hill reaction activity and growth rate of cells in barley under saline rhizosphere [24].…”
Section: Introductionmentioning
confidence: 99%